Benign familial hyperphosphatasaemia as a cause of unexplained increase in plasma alkaline phosphatase activity. Issue 8 (August 1993) - Rosalki, S B; Foo, A Y; Dooley, J S
Abstract : AIMS--To consider a possible genetic origin for the persistent unexplained increase in plasma alkaline phosphatase (ALP) in five non-related patients referred over an 18 month period. METHODS--Plasma ALP isoenzyme activities were measured in patients and their first degree relatives. RESULTS--In each patient there was a noticeable increase in intestinal plasma ALP, either alone or accompanied by an increase in bone or liver ALP. Family studies showed an unexpected increase in plasma ALP and similar isoenzyme changes in first degree relatives. The findings were consistent with autosomal dominant inheritance. CONCLUSION--Inherited raised plasma ALP activity is a reasonably common cause of persistent unexplained hyperphosphatasaemia which deserves wider recognition.